2016
DOI: 10.1001/jamaoto.2015.3123
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bronchoscopy in Percutaneous Dilational Tracheostomy

Abstract: Percutaneous dilational tracheostomy can be performed with similarly low complication rates with or without the use of bronchoscopy. Discontinuing the use of bronchoscopy in these procedures appears to be a safe, cost-effective alternative with reassuring outcomes and low complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 33 publications
1
49
0
Order By: Relevance
“…Most of the data available is from retrospective studies. The studies [109][110][111][112][113][114][115] compared PDT with and without bronchoscopy in various clinical subset and all of them concluded that PDT can be safely performed even without the aid of bronchoscope Indian Journal of Critical Care Medicine, January 2020;24(Suppl 1)…”
Section: Does the Use Of Fiberoptic Bronchoscope (Fob) While Performimentioning
confidence: 99%
“…Most of the data available is from retrospective studies. The studies [109][110][111][112][113][114][115] compared PDT with and without bronchoscopy in various clinical subset and all of them concluded that PDT can be safely performed even without the aid of bronchoscope Indian Journal of Critical Care Medicine, January 2020;24(Suppl 1)…”
Section: Does the Use Of Fiberoptic Bronchoscope (Fob) While Performimentioning
confidence: 99%
“…4 Iatrogenic injury from endotracheal and/or tracheostomy tubes occurs more frequently than other etiologies. 4,7 Studies show endotracheal tube sizes larger than 7.5 place patients at higher risk for tracheal stenosis and posterior glottic stenosis. 8,9 Additionally, comorbidities adversely affecting wound healing, including diabetes, were found to be intrinsic risk factors for glottic stenosis and associated with iatrogenic LTS.…”
Section: Introductionmentioning
confidence: 99%
“…The cost per procedure with a multiple‐use bronchoscope is difficult to calculate and may vary significantly between institutions since many variables as frequency of uses per device, costs for maintenance, and decontamination influence the overall costs. Nevertheless, it has been estimated to be at least 400€ per use by some institutions . In our institution with a high frequency of use per bronchoscope the costs are lower and are estimated at about 100€ per use which is approximately the price of a VST.…”
Section: Discussionmentioning
confidence: 75%